Feasibility Analysis of Tilapia Aquaculture Base on Agribisiness Aproach in Pinrang Regency, South Sulawesi - Citra Ayunanda; Irmayani, Irmayani; Abd Rahim (Cita konsultindo, 2024)
The demand in both the domestic and international markets for chili commodities in the future is expected to increase along with the rising population and income levels, which can impact the income of chili farming and ultimately affect household income. This research aims to analyze the impact of planting bird's eye chili on the rice field bunds on the household income of farmers. This study employs a quantitative method to understand whether and how the additional income from bird's eye chili can enhance the total income of farmers' households. The results of this study indicate that planting bird's eye chili can provide an additional source of income for farmers, thereby increasing their total income. The research results show that the average profit received by chili farming on the rice field embankments is Rp. 1,080,000 per year. Based on the business feasibility calculations, the R/C ratio obtained is 3.9. It can be concluded that chili farming in the rice fields of Benteng Village, Patampanua District, Pinrang Regency is feasible for development.